Análise cienciométrica sobre fungos endofíticos e fungos do solo de uma área de Quirinópolis, Goiás, Brasil - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The Brazil has an immense diversity of ecosystems, reflecting its vast territory and variety of climates, reliefs and hydrography. These ecosystems are highly devastated due to the increase in consumer demands and the imminent process of desertification, especially in the Caatinga and Cerrado biomes, influenced by the expansion of agriculture. Although the macrobiodiversity of biomes has been widely studied, knowledge about their microbiota, particularly endophytic fungi, is still limited. These fungi live inside plants in symbiosis and contribute to sustainability by promoting plant growth and resistance to diseases and water stress, as well as producing bioactive compounds for the pharmaceutical and agrochemical industries. Therefore, this study aims to evaluate the scientific production on endophytic fungi in Brazil and by biome, with the objective of elucidating trends and gaps and understanding the regional character of the studies of each biome, through a scientometric analysis with systematic review, as well as investigating the species that occur in the soil of an area in the cerrado of Goiás, as a way of contributing to the knowledge of the fungal community of the Serra da Confusão do Rio Preto region, Quirinópolis, Goiás, Brazil. To achieve these objectives, we performed a scientometric analysis using the Web of Science database, in which 79 articles published distributed irregularly among the biomes, from 1994 to 2024 on endophytic fungi in Brazil were analyzed. The scientometric analysis revealed a significant increase in the number of publications on endophytic fungi in Brazil over the period evaluated, primarily in the Amazon biome, with a predominant focus on secondary metabolites and taxonomic aspects. However, there was a lack of studies on the variety and recurrence of these fungi, their industrial applications, and ecological restoration practices. The incipient studies in the Pampa, Pantanal, and Atlantic Forest biomes indicated a promising area for future research. At the same time, we conducted a study of isolation and visual identification of filamentous fungi from soil samples of four regions with different levels of anthropogenic disturbance, namely: area 1 - Disturbed Spring, presence of riparian vegetation in an area smaller than that provided for in Law No. 12,651 (BRASIL, 2012); area 2 - Spring with pasture; area 3 - Spring with sugarcane cultivation and area 4 - Constructions near the springs, evaluating the disposition and variety of fungi with endophytic potential at different depths (0-10, 10-20, 20-30 cm). Furthermore, the results of the field study demonstrated that area preservation influences fungal availability and depth influences species variety. The endophytic genera Aspergillus and Penicillium were identified in surface soil samples from areas 1 and 2. Furthermore, they were observed to play a crucial role in plant phosphorus acquisition, which is often limiting in Brazilian soils, especially in the Cerrado. They also played a crucial role in Acremonium, Scedosporium, and Ceratobasidium (also mycorrhizal), Arthrographis, which has bioremediation potential, and the pathogens Nannizzia and Histoplasma.
Scientometric analysis of endophytic fungi and soil fungi in an area of Quirinópolis, Goiás, Brazil.
Keywords: Aspergillus; Biodiversidade Brasileira; Funga do Solo; Penicillium; Fungos Endofíticos.; Aspergillus.; Biodiversidade Microbiana.; Ecossistemas Brasileiros.; Bioma Cerrado.; Restauração ecológica.; Brazilian biodiversity; Fungi from the Soil; CIENCIA DO SOLO::MICROBIOLOGIA E BIOQUIMICA DO SOLO